Method for rapidly testing content of each component in sodium alginate compound

By measuring the conductivity and viscosity of the sodium alginate complex, combining the beat concentration formula and water hardness value, the content of each component is quickly and accurately calculated, solving the problems of difficulty and large errors in traditional acidification methods, and achieving a more efficient test method.

CN119827713AActive Publication Date: 2025-04-15SHANDONG JIEJING GROUP CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411974922.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

It is difficult to quickly and accurately measure the content of each component in the sodium alginate complex, especially when the sodium alginate content is less than 15%, and the error is large.

Method used

The sodium alginate complex is dissolved to form a 1% concentration of the raw paste to be measured, its conductivity and viscosity are measured, and the content of each component is calculated based on the beat concentration formula and the water hardness value.

Benefits of technology

The rapid and accurate measurement of the content of each component of the sodium alginate complex with unknown proportions is achieved, reducing the test time and complexity, with an error of less than 1.65%, which is better than the traditional acidification method.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for rapidly testing the content of each component in a sodium alginate compound, and the method comprises the following steps: S1, dissolving the sodium alginate compound with pure water to obtain a to-be-tested raw paste with the dissolution concentration of 1%, and testing the conductivity of the to-be-tested raw paste as A ms / cm and the viscosity as b cp; s2, presetting the beating target viscosity at room temperature as a, and calculating the beating concentration w according to a beating concentration formula; s3, determining the highest water hardness value of the printing and dyeing water as n mg / L, and calculating the content z of sodium hexametaphosphate in the sodium alginate compound according to the amount of sodium hexametaphosphate required for neutralizing the content of calcium and magnesium ions in the water, wherein z = (3n / 10000) / w / 100; s4, calculating the content x of sodium alginate according to a formula x = (11-A-7. 5z) / 9; and calculating the content z of the anhydrous sodium sulphate according to y = 1-x-z. Compared with an acidification method, the method has the advantages that the content of each component of the printing and dyeing sodium alginate compound with an unknown ratio can be more accurately measured, the test speed is higher, and the test method is simpler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of textile printing and dyeing, and particularly relates to a method for quickly testing the content of each component in a sodium alginate complex. Background Art

[0002] The sodium alginate complex commonly used in the printing and dyeing industry is usually composed of sodium alginate, sodium sulfate and sodium hexametaphosphate. Compared with the use of sodium alginate to prepare the original paste, the sodium alginate complex dissolves faster and is not easy to clump during the dissolution process. In order to obtain the most suitable sodium alginate complex ratio, it is usually necessary to purchase a variety of commercially available products for testing experiments. After determining the best product, the product formula is deciphered to obtain a preliminary plan close to the optimal ratio, and then experimental optimization is carried out on this basis to determine the final product formula.

[0003] However, the commonly used method for measuring the sodium alginate content is usually an acidification method, which first prepares a 1% concentration solution, then weighs part of the solution and adds a certain concentration of hydrochloric acid to convert the sodium alginate into alginate fibers and precipitate them, then filters out the alginate fibers and uses pure alcohol to dehydrate the alginate, and then low-temperature drying (temperature below 50°C) is performed on the dehydrated alginate for more than 8 hours, which is time-consuming and laborious. In addition, when we use the acidification method to test the sodium alginate content in the sodium alginate complex, we also find that when the sodium alginate content in the sodium alginate complex is lower than 15%, the alginate fibers formed after adding hydrochloric acid are not formed, and the alginate fibers cannot be filtered out, which leads to the inability of the acidification method to measure the sodium alginate content when the sodium alginate content is lower than 15%; and the error of measuring the sodium alginate content by the acidification method is about 5%, which also affects the judgment of the sodium alginate content.

[0004] Therefore, the traditional acidification method is difficult to adapt to the requirements for determining the content of sodium alginate and other components in sodium alginate complexes for printing and dyeing with unknown proportions. Summary of the invention

[0005] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to provide a method for quickly testing the content of each component in a sodium alginate complex. Compared with the acidification method, the method can more accurately measure the content of each component of a sodium alginate complex for printing and dyeing with an unknown ratio, and the test speed is faster and the test method is simpler.

[0006] In order to achieve the above object, the present invention discloses a method for quickly testing the content of each component in a sodium alginate complex, wherein the sodium alginate complex is composed of sodium alginate, sodium sulphate and sodium hexametaphosphate, and the method comprises the following steps:

[0007] S1: dissolving the sodium alginate complex in pure water to obtain a test paste, the dissolution concentration is 1%, and the test results show that the conductivity of the test paste is A ms / cm and the viscosity is b cp;

[0008] S2: The target viscosity of pulping at room temperature is set to a, and the pulping concentration W is calculated according to the pulping concentration formula;

[0009] S3: Determine the highest water hardness value of the printing and dyeing water as n mg / L, and calculate the content of sodium hexametaphosphate in the sodium alginate complex according to the amount of sodium hexametaphosphate required to neutralize the calcium and magnesium ions in the water: z=(3n÷10000)÷w÷100;

[0010] S4: According to the formula x=(11-A-7.5z)÷9, calculate the content x of sodium alginate; according to y=1-Xz, calculate the content z of sodium sulphate.

[0011] Preferably, the target viscosity of pulping is a=10000cp.

[0012] Preferably, the beating concentration formula is w=(a÷0.9654÷b)∧(1÷3.2769)÷100.

[0013] Preferably, the water hardness value of the dyeing and printing water measured in step S3 in terms of CaCO3 is n=448 mg / L.

[0014] Preferably, step S1 is to test the conductivity of the original paste at 20°C.

[0015] Compared with the prior art, the advantages and positive effects of the present invention are: providing a method for quickly testing the content of each component in a sodium alginate complex. Compared with the acidification method, the method can more accurately measure the content of each component of a sodium alginate complex for printing and dyeing with an unknown ratio, and the testing speed is faster and the testing method is simpler. DETAILED DESCRIPTION

[0016] The present invention is described in detail below by means of exemplary embodiments. However, it should be understood that the structures and features in one embodiment may also be beneficially combined in other embodiments without further description.

[0017] A method for quickly testing the content of each component in a sodium alginate complex, wherein the sodium alginate complex consists of sodium alginate, sodium sulphate and sodium hexametaphosphate, and the method comprises the following steps:

[0018] S1: dissolving the sodium alginate complex in pure water to obtain a test paste, the dissolution concentration is 1%, and the test results show that the conductivity of the test paste is A ms / cm and the viscosity is b cp;

[0019] S2: The target viscosity of pulping at room temperature is set to a, and the pulping concentration W is calculated according to the pulping concentration formula;

[0020] S3: Determine the highest water hardness value of the printing and dyeing water as n mg / L, and calculate the content of sodium hexametaphosphate in the sodium alginate complex according to the amount of sodium hexametaphosphate required to neutralize the calcium and magnesium ions in the water: z=(3n÷10000)÷w÷100;

[0021] S4: According to the formula x=(11-A-7.5z)÷9, calculate the content x of sodium alginate; according to y=1-Xz, calculate the content y of sodium sulphate.

[0022] After testing, the conductivity of 1% sodium alginate in pure water at 20°C is 2ms / cm, the conductivity of 1% sodium sulfate is 11ms / cm, and the conductivity of 1% sodium hexametaphosphate is 3.5ms / cm. Therefore, the conductivity of the original paste to be tested obtained in step S1 is A=2x+11y+3.5z, where x is the content of sodium alginate, y is the content of sodium sulfate, z is the content of sodium hexametaphosphate, x+y+z=1, and thus x=(11-A-7.5z)÷9.

[0023] In view of the fact that sodium hexametaphosphate in the sodium alginate complex is used to soften water, the method calculates the content of sodium hexametaphosphate based on this, and determines the highest water hardness value of water for printing and dyeing as nm mg / L through water hardness detection. After experimental research, the content of sodium hexametaphosphate required to fully soften the water with a hardness value of nm mg / L is z=(3n÷10000)÷w÷100, wherein w is the beating concentration of the original paste to be tested obtained in step S1. When the target beating viscosity a is determined and the viscosity of the original paste to be tested is measured as b cp by a viscosity testing device, the beating concentration w can be calculated by the beating concentration formula, and then w is substituted into the above formula to calculate the content z of sodium hexametaphosphate, and then when the conductivity of the original paste to be tested is measured, the content x of sodium alginate and the content y of glauber salt are calculated, and the content of each component in the sodium alginate complex can be quickly measured.

[0024] During the implementation of this method, only the viscosity and conductivity of the original paste to be tested, which is prepared from the sodium alginate complex, and the hardness of the water used for printing and dyeing need to be simply tested, and the content of each component in the sodium alginate complex can be determined by calculation, providing a simple and efficient testing method for optimizing product formulas. This method is not affected by the molding state of the sodium alginate fiber in the acidification test, and solves the problem that the acidification method cannot measure the sodium alginate content in the complex when the sodium alginate content is less than 15%, greatly shortening the time used to detect the content of each component in the sodium alginate complex.

[0025] Specifically, the sodium alginate complex needs to be made into a high-concentration raw paste during the printing and dyeing application process. The raw paste pulping viscosity is usually greater than 10,000 cp (at room temperature). In order to make the test results more accurate, the target pulping viscosity a is set to 10,000 cp.

[0026] Specifically, in order to ensure the accuracy of the test, the beating concentration formula of step S2 is w=(a÷0.9654÷b)∧(1÷3.2769)÷100.

[0027] Specifically, we conducted a nationwide water quality survey and found that the water quality in the north is relatively hard. We selected water used in different printing and dyeing factories in the north and conducted water hardness testing. The worst water quality was 448 mg / L (measured in CaCO3). In order to ensure the softening effect, the hardness value n of the water used in printing and dyeing was set to 448 mg / L.

[0028] Specifically, in order to determine the test result more accurately, step S1 is to test the conductivity of the original paste at 20°C.

[0029] Example 1

[0030] The sodium alginate complex to be tested in Example 1 is prepared, and is composed of the following components by weight percentage: 20% sodium alginate, 77.5% sodium sulfate, and 2.5% sodium hexametaphosphate. (The percentages in the examples of the present invention are all by mass percentage)

[0031] A method for rapidly testing the content of each component in a sodium alginate complex comprises the following steps:

[0032] S1: dissolving the obtained sodium alginate complex to be tested in pure water to obtain a raw paste to be tested, the dissolution concentration is 1%, and the conductivity of the raw paste to be tested is A=8.9ms / cm and the viscosity is b=21cp;

[0033] S2: The target viscosity of pulping at room temperature is preset to 10000cp, and the pulping concentration is calculated according to the pulping concentration formula: w = (a÷0.9654÷b)∧(1÷3.2769)÷100 = (10000÷0.9654÷21)∧(1÷3.2769)÷100 = 6.64%;

[0034] S3: According to the test statistics, the highest water hardness value of the printing and dyeing water is determined to be n=448 mg / L. According to the amount of sodium hexametaphosphate required to neutralize the calcium and magnesium ions in the water, the content of sodium hexametaphosphate in the sodium alginate complex is calculated to be z=(3n÷10000)÷w÷100=(3×448÷10000)÷6.64%÷100=2.02%;

[0035] S4: According to the formula x=(11-A-7.5z)÷9=(11-8.9-7.5×2.02%)÷9=21.65%, the sodium alginate content x=21.65% is calculated; according to y=1-Xz=1-21.65%-2.02%=76.33%, the glauber powder content y=76.33% is calculated.

[0036] The mass percentages of the components in the sodium alginate complex to be tested measured by the above method are: sodium alginate 21.65%, sodium sulfate 76.33%, sodium hexametaphosphate 2.02%. The error is less than 1.65%, which is much smaller than the 5% error of the acidification method. It can be seen that the method of this embodiment is more accurate than the acidification method test results.

[0037] Example 2

[0038] The sodium alginate complex to be tested in Preparation Example 2 is composed of the following components in percentage by weight: 55% sodium alginate, 41% glauber salt, and 3.5% sodium hexametaphosphate.

[0039] A method for rapidly testing the content of each component in a sodium alginate complex comprises the following steps:

[0040] S1: dissolving the obtained sodium alginate complex to be tested in pure water to obtain a raw paste to be tested, the dissolution concentration is 1%, and the conductivity of the raw paste to be tested is A=5.61ms / cm and the viscosity is b=122cp;

[0041] S2: The target viscosity of pulping at room temperature is preset to 10000cp, and the pulping concentration is calculated according to the pulping concentration formula: w = (a÷0.9654÷b)∧(1÷3.2769)÷100 = (10000÷0.9654÷122)∧(1÷3.2769)÷100 = 3.88%;

[0042] S3: According to the test statistics, the highest water hardness value of the printing and dyeing water is determined to be n=448 mg / L. According to the amount of sodium hexametaphosphate required to neutralize the calcium and magnesium ions in the water, the content of sodium hexametaphosphate in the sodium alginate complex is calculated to be z=(3n÷10000)÷w÷100=(3×448÷10000)÷3.88%÷100=3.46%;

[0043] S4: According to the formula x=(11-A-7.5z)÷9=(11-5.61-7.5×3.46%)÷9=57%, the sodium alginate content x=57% is calculated; according to y=1-Xz=39.54%, the glauber powder content y=39.54% is calculated.

[0044] Example 3

[0045] The sodium alginate complex to be tested in Example 3 is prepared, which is composed of the following components in percentage by weight: 80% sodium alginate, 15% sodium sulphate, and 5% sodium hexametaphosphate.

[0046] A method for rapidly testing the content of each component in a sodium alginate complex comprises the following steps:

[0047] S1: dissolving the obtained sodium alginate complex to be tested in pure water to obtain a raw paste to be tested, the dissolution concentration is 1%, and the conductivity of the raw paste to be tested is A=3.11ms / cm and the viscosity is b=700cp;

[0048] S2: The target viscosity of pulping at room temperature is preset to 10000cp, and the pulping concentration is calculated according to the pulping concentration formula: w = (a÷0.9654÷b)∧(1÷3.2769)÷100 = (10000÷0.9654÷700)∧(1÷3.2769)÷100 = 2.28%;

[0049] S3: According to the test statistics, the highest water hardness value of the printing and dyeing water is n=448 mg / L. According to the amount of sodium hexametaphosphate required to neutralize the calcium and magnesium ions in the water, the content of sodium hexametaphosphate in the sodium alginate complex is calculated as z=(3n÷10000)÷w÷100=(3×448÷10000)÷2.28%÷100=5.89%;

[0050] S4: According to the formula x=(11-A-7.5z)÷9=(11-3.11-7.5×5.89%)÷9=82.76%, the sodium alginate content x=82.76% is calculated; according to y=1-xz=11.35%, the glauber powder content y=11.35% is calculated.

[0051] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for rapidly testing the content of each component in a sodium alginate complex, wherein the sodium alginate complex is composed of sodium alginate, sodium sulphate and sodium hexametaphosphate, characterized in that: The method comprises the following steps: S1: dissolving the sodium alginate complex in pure water to obtain a test paste, the dissolution concentration is 1%, and the test results show that the conductivity of the test paste is A ms / cm and the viscosity is b cp; S2: The target viscosity of pulping at room temperature is set to a, and the pulping concentration W is calculated according to the pulping concentration formula; S3: Determine the highest water hardness value of the printing and dyeing water as n mg / L, and calculate the content of sodium hexametaphosphate in the sodium alginate complex according to the amount of sodium hexametaphosphate required to neutralize the calcium and magnesium ions in the water: z=(3n÷10000)÷w÷100; S4: According to the formula x=(11-A-7.5z)÷9, calculate the content x of sodium alginate; according to y=1-xz, calculate the content z of sodium sulphate.

2. The method for rapidly testing the content of each component in a sodium alginate complex according to claim 1, characterized in that: The target viscosity of the pulping is a=10000 cp.

3. The method for rapidly testing the content of each component in a sodium alginate complex according to claim 1, characterized in that: The formula for pulping concentration is w = (a÷0.9654÷b)∧(1÷3.2769)÷100.

4. The method for rapidly testing the content of each component in a sodium alginate complex according to claim 1, characterized in that: The water hardness value of the dyeing water measured in step S3 in terms of CaCO3 is n=448 mg / L.

5. The method for rapidly testing the content of each component in a sodium alginate complex according to claim 1, characterized in that: Step S1 is to test the conductivity of the original paste at 20°C.

Citation Information

Patent Citations

  • Method for measuring sodium alginate content

    CN107219175A

  • Method for rapidly preparing dye sodium alginate thickening with target viscosity through one-step process

    CN107254788A

  • Polysaccharide concentration detection method

    CN113607779A

  • Modified alginic acid derivative and application thereof as cotton fabric digital printing pretreatment agent

    CN113861308A

  • Alginate, method for measuring monosaccharide residue content of alginic acid and application of alginate and method for measuring monosaccharide residue content of alginic acid

    CN116990442A